MOTIF DAN MAKNA DIRI ATLET ANGKAT BESI WANITA DI PEKANBARU (Studi Pada Atlet PABBSI Riau) - Widya Ramalia Putri; Welly Wirman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Generally, weightlifting is known as man’s sport. However, by time, gender equality has been spread from various sport profession resulting particularly female weightlifter. Becoming a female weightlifter is not an easy profession. In fact, there is no woman who was born and named instantly as an athlete. The physical activity that was done by woman nowadays has changed the feminist image towards competence and physical development. The aim of this research is to idemtify the motive, the self-meaning and the meaning of weightlifting profession for female in Pekanbaru.This research was conducted through qualitative method with phenomenological approach. The subject of this research was five female weightlifter in Pekanbaru that was chosen by purposive technique. The data collection technique was collected through interview, observation, and research documentation. To achieve the validity of data in this study, researcher used extension of participation and triangulation.The initial result for because motive showed that female weightlifter was motivated through joining other, curiosity and parents boast. Besides for in order to motive the data showed that they want to be a weightlifting coach with better achievement, and having next generation. Secondly, female weightlifter interprets themselves as a great and strong woman Thirdly, female weightlifter defines that this weightlifter profession is a hard profession with income.Keywords: Female Weightlifter, Motive, Selft Meaning, Meaning of Profession